Inflammatory Response of Human Peripheral Blood Mononuclear Cells and Osteoblasts Incubated With Metallic and Ceramic Submicron Particles - Klinder, Annett; Seyfarth, Anika; Hansmann, Doris; Bader, Rainer; Jonitz-Heincke, Anika (Frontiers in Immunology, 2018)
Inflammatory reactions associated with osteolysis and aseptic loosening are the result of wear particles generated at the articulating surfaces of implant components. The aim of the present study was to analyze the biological response of human osteoblasts and PBMCs after exposure to metallic and alumina ceramic particles regarding cellular differentiation, cytokine release and monocyte migration. Cells were exposed to particles (0.01 mg/ml, 0.05 mg/ml) from an alumina matrix composite (AMC) and a CoCr28Mo6 alloy with an average size of 0.5 µm over 48 h and 96 h. The expression rates of osteogenic (Col1A1, ALP) and pro-osteoclastic (RANK, Trap5b) differentiation markers as well as pro-osteolytic mediators (MMP-1, TIMP-1, IL-6, IL-8, MCP-1) were determined and soluble protein concentrations of active MMP-1, IL-6, IL-8 and pro-collagen type 1 in cell culture supernatants were evaluated. Additionally, the capacity of particle-treated osteoblasts to attract potentially pro-inflammatory cells to the site of particle exposure was investigated by migration assays using osteoblast-conditioned media. The cellular morphology and metabolism of human osteoblasts and adherent PBMCs were influenced by particle type and concentration. In human osteoblasts, Col1A1 expression rates and protein production were significantly reduced after exposing cells to the lower concentration of CoCr and AMC particles. Exposure to AMC particles (0.01 mg/ml) resulted in increased mRNA levels of RANK and Trap5b in adherent PBMCs. For MMP-1 gene expression, elevated levels were more prominent after incubation with CoCr compared to AMC particles in osteoblasts which was not reflected by the protein data. IL-6 and IL-8 mRNA and protein was induced in both cell types after treatment with AMC particles whereas exposure to CoCr particles resulted in significantly upregulated IL-6 and IL-8 protein contents in PBMCs only. Exposure of osteoblasts to CoCr particles reduced the chemoattractant potential of osteoblast-conditioned medium. Our results demonstrated distinct effects of AMC and CoCr particles in human osteoblasts and PBMCs. More complex cell models are required to further evaluate the impact of cellular interactions between different cell types during particle exposure.